SIFAT PENGGERGAJIAN DAN PENGERJAAN BEBERAPA JENIS KAYU HTI - Dede Rohadi; Bakir Ginoga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
This paper reports the studies on sawmilling woodworking properties of 3 plantation wood species. derived from some plantation areas in Java, Logs of K.emiri (Aleurites molluccana). tusam (Pinus merkusii) and Piaus oocarpa were sawn using a 44 inch bandsaw to produce various size of boards. Following drying to approximately 1 5% of moisture content. the boardh were observed for their machining properties. The dried boards were processed further into varaous end products and furnitures.Sawmilling trials shorwed that the average sawn timber recoveries for the respective species were 45%, 60% and 73%. regardless to the limited length and width of the resulted boards from the sawmilling process, which were due to the small log diameters, a satisfactory jointing board can be produced through the application of finger and edge jointing machines.All of the species showed to have good machining properties and good workability. Either the fresh logs or wood cants can beutilized for producing various tuming products. handicrafts or even furnitures such as tables and chairs. The study showed the potential utilization of plantation materials for various end products.